A MODEL OF BLOCKCHAIN TECHNOLOGY IN PAYMENT SETTLEMENT IN ENERGY SUPPLY INDUSTRY - MOHAMED RIMSAN, MOHAMED MOHIDEEN (2021)
The smart energy infrastructure develops from a smart grid network to an energy internet.